LEVEL OF EFFECTIVENESS OF COW MANURE COMPOST IN JOGOROGO VILLAGE - Fiilaila Isra' Mahastya Mulia; Zaenal Abidin; Avicena Sakufa Marsanti (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2023)
With the high total population of cattle each year, it will also cause a high amount of cow dung generation. Jogorogo village is an area that has a lot of cattle breeders. It is necessary to make compost from cow dung to reduce the generation of cow dung. In addition to meeting the nutritional needs of plants, making compost will reduce the generation of waste and livestock manure that accumulates to pollute the environment. Because the pH of cow dung is too acidic, additional materials are needed, namely sawdust and rice straw. The purpose of this study was to determine the effectiveness of nitrogen and phosphorus levels in compost from cow dung. The study design used in this research is One shot case study. During the composting process, physical parameters (texture, color, odor, temperature) were measured and also chemical parameters were examined for the nutrient content of the compost (Nitrogen, Phosphorus, organic C and C/N ratio). Analyzed using the Kruskall-Wallis test and then continued with the Mann-Whitney. There are differences in the effectiveness of N levels, P levels and C/N ratio levels between formula 1 and formula 2. The two formulas tested were four levels that almost met all of the requirements, namely in formula 2. Furthermore, from the two groups of formulas, formula 2 required an average time 29 days on average so it is more effective than formula 1 which takes 30 days.